The impact of legal expertise on moral decision-making biases - Báez, Sandra (2020)
Traditional and mainstream legal frameworks conceive law primarily as a purely rational practice, free from affect or intuition. However, substantial evidence indicates that human decision-making depends upon diverse biases. We explored the manifestation of these biases through comparisons among 45 criminal judges, 60 criminal attorneys, and 64 controls. We examined whether these groups’ decision-making patterns were influenced by (a) the information on the transgressor’s mental state, (b) the use of gruesome language in harm descriptions, and (c) ongoing physiological states. Judges and attorneys were similar to controls in that they overestimated the damage caused by intentional harm relative to accidental harm. However, judges and attorneys were less biased towards punishments and harm severity ratings to accidental harms. Similarly, they were less influenced in their decisions by either language manipulations or physiological arousal. Our findings suggest that specific expertise developed in legal settings can attenuate some pervasive biases in moral decision processes.